(untitled) (ACME, 2020)
Fictions are credited with a significant power to change our attitudes and behaviours. But do they actually have such a power? What precisely can they do? And what role does imagination play in that? In this paper, I address these questions drawing on some important studies on the psychology of fictional engagement, which go under the label of ‘transportation studies’. These studies, I argue, show that fiction’s influences are made possible by some basic features of our cognitive architecture, such as the capacity that imagination has to interact with our emotional system, on the one hand, and some standard mechanisms of belief formation and revision, on the other hand. From this discussion I also draw a more general methodological lesson concerning the fruitfulness of the interactions between philosophy and psychology when it comes to investigating our engagement with fiction: if philosophers cannot ignore the work that psychologists have done in this area, psychologists can benefit from philosophers’ work of conceptual analysis, which provides a broader range of explanatory options for their data.